Myelofibrosis-Related Arthritis Successfully Treated with Hydroxyurea - Xavier Guillot; Marius Moldovan; Claire Vidon; Daniel Wendling (Case Reports in Rheumatology)
A 62-year-old woman suffering from one-year lasting, nonerosive peripheral arthritides with general health impairment and high acute-phase reactant levels was admitted to rheumatology department. The patient had suffered from chronic polyarthralgia and a thrombocytosis had been discovered 9 years before, with a recent increase in platelet count. All immunological blood tests were negative. Corticosteroid and methotrexate treatments improved pain, swollen joint count, and systemic inflammation. However, joints remained stiff and painful with two swollen wrists and persistent thrombocytosis. An iliac bone marrow biopsy was performed, showing primary myelofibrosis. Hydroxyurea treatment (500 mg per day) allowed to achieve complete and prolonged clinical and biological remission. After 6 months, a new disease flare occurred. The patient reached remission again after hydroxyurea dose increased to 1500 mg per day. This supports the hypothesis of idiopathic myelofibrosis-associated seronegative polyarthritis. This is the first reported case in which haemopathy-targeted treatment using hydroxyurea induced arthritis remission.